2023
DOI: 10.1027/1015-5759/a000700
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Quality in Higher Education

Abstract: Abstract. Teaching quality is a crucial factor within higher education. Research on this topic often requires assessing teaching quality as a global construct through self-reports. However, such instruments are criticized due to the lack of alignment between teacher and student reports of instructional practices. We argue that while teachers might over- or under-estimate specific dimensions of teaching quality, the aggregation of these dimensions in the form of overarching teaching quality well reflects differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Studies revealed differences in teacher knowledge according to their gender [25,49,75], age [40,49], teaching experience [20,49] and educational level [48]. Gender and teaching experience are also related to self-reported teaching quality [21,65]. For these reasons, sociodemographic questions and questions regarding teachers' experience were included in the questionnaire.…”
Section: Methods 41 Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies revealed differences in teacher knowledge according to their gender [25,49,75], age [40,49], teaching experience [20,49] and educational level [48]. Gender and teaching experience are also related to self-reported teaching quality [21,65]. For these reasons, sociodemographic questions and questions regarding teachers' experience were included in the questionnaire.…”
Section: Methods 41 Participantsmentioning
confidence: 99%
“…This study adopted a cognitive perspective on teacher knowledge and teaching quality which, in contrast with a situated perspective proposes that those constructs can be "measured independently from the classroom context in which it is used, most often through a test" [23:22]. Daumiller et al [21] showed that self-reported and student-reported teaching quality are highly correlated. Hence, similarly to previous research on teaching quality and teacher knowledge, this study relies on self-reported measures from the perspective of the teachers [21,58,89].…”
Section: Research Approach and Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the literature [16] analyzed that the presence of learning disabilities in the higher education process can make the standard of quality education suffer and that setting appropriate educational goals can help students with learning disabilities to receive a higher quality education. The literature [17] discusses the importance of quality education in higher education, analyzes the importance of teachers' quality education based on the quality of their teaching, and considers the influence of bias and inequity variables on the results, respectively. The literature [18] analyzed quality education results in the College of Education of the Public University of Ghana from 2012 to 2017 to show that best management practices can effectively enhance teaching and learning efficiency and thus promote quality education.…”
Section: Introductionmentioning
confidence: 99%